Objective structured therapeutic examination (OSTE) for the assessment of psychodynamic intervention competencies in psychotherapy trainees - Nikendei, Christoph; Montan, Inka; Stölting, Julia; Ehrenthal, Johannes C.; Storck, Timo; Taubner, Svenja; Friederich, Hans-Christoph; Schauenburg, Henning; Schultz, Jobst-Hendrik; Dinger, Ulrike (Training and education in professional psychology, 2025)
Objective structured clinical examinations have a long tradition in medical education. In psychotherapy training, this format is on the rise. The aim of this study was to prove reliability and feasibility of an objective structured therapeutic examination (OSTE) for the assessment of psychodynamic intervention competencies. Twelve psychotherapy trainees took part in a formative four-station OSTE designed to assess specific psychodynamic intervention competencies (confrontation, affect differentiation, empathetic validation, resistance interpretation). Four standardized patient scenarios were developed to evaluate the respective psychodynamic interventions at the video-taped stations. Performance was assessed using observer-rated intervention-specific and general communication rating scales. Interrater reliability of four video-raters and reliability of the OSTE were determined. Trainees rated feasibility, face validity, and perceived stress on Likert Scales. Interrater reliability (Kendall’s W) referring to intervention-specific competencies was 0.85 in the mean and 0.72 for general communication competencies, respectively. Cronbach’s α of the intervention-specific rating scale was .74 on average and .83 for the general communication scale, respectively. Extrapolated to a 10-station OSTE, Cronbach’s α was estimated as .88 for the intervention-specific rating scale and .92 for the general communication rating scale. Participants evaluated the OSTE format as appropriate to mirror their therapeutic competencies. An OSTE for the assessment of psychodynamic intervention competencies in psychodynamic psychotherapy training proves to be reliable and feasible. (PsycInfo Database Record (c) 2025 APA, all rights reserved)